2011
DOI: 10.1039/c0cp02638g
|View full text |Cite
|
Sign up to set email alerts
|

Ground and excited state communication within a ruthenium containing benzimidazole metallopolymer

Abstract: This version is available at https://strathprints.strath.ac.uk/30862/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…This is primarily due to the high sensitivity, relatively high ECL efficiency and wide dynamic range afforded by transition metal based luminophores [1,4,14,15]. For bio-sensing and diagnostic applications current research strategies for ruthenium based platforms focus on optimising the ECL efficiency, i.e., photons emitted per electron passed [16,17]. Important approaches include new co-reactants and altering the electrochemical characteristics of the material itself so as to increase the charge transfer rate to produce more luminophores per unit time.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the high sensitivity, relatively high ECL efficiency and wide dynamic range afforded by transition metal based luminophores [1,4,14,15]. For bio-sensing and diagnostic applications current research strategies for ruthenium based platforms focus on optimising the ECL efficiency, i.e., photons emitted per electron passed [16,17]. Important approaches include new co-reactants and altering the electrochemical characteristics of the material itself so as to increase the charge transfer rate to produce more luminophores per unit time.…”
Section: Introductionmentioning
confidence: 99%
“…This pH was chosen as a near neutral pH is highly desirable for biological applications. The reaction scheme for the generation of ECL between a ruthenium containing metallopolymer and oxalic acid has been well documented [14][15][16]24 and occurs according to the reaction scheme; 5,12,19 [Ru(bpy) 2 …”
mentioning
confidence: 99%
“…Forster group had reported that the electrochemiluminescent (ECL) properties of some luminescent metal centers, including [Ru (bpy) 3 ] 2+ and [Os(bpy) 3 ] 2+ , can be significantly modulated by encapsulation within a conducting polymer composite film. The conducting polymer, such as polyaniline (PANI), polypyrrole (PPy) or benzimidazole based polymers, can dramatically improve the charge-transfer rates between the metal centers, thus increasing the ECL efficiency of the luminophore [27][28][29][30]. So far, the quenching effect of PANI on ECL signal has not been investigated and applied in ECL sensing field.…”
Section: Introductionmentioning
confidence: 99%